Análisis de la actividad de ascorbato oxidasa durante el desarrollo de la planta de frijol (Phaseolus vulgaris L. var. Flor de Mayo) - Herrera Gómez, Palmira (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
In Mexico, beans have a great economic and nutritional importance, being the most consumed legume in the country (SAGARPA), hence the fundamental of the study of its development, which is divided into five phenological stages: germination, vegetative growth, flowering and grain filling. This development is affected by environmental factors, such as lack of water. In the development of plants such as onions, tobacco and peas, it has been seen that the enzyme Ascorbate Oxidase (AO) plays an important role in cell expansion and differentiation, in the control of the redox state of apoplast and even in the regulation of the availability of oxygen in the cells depending on their high or low respiratory rate. This is because the AO carries out the reduction with four electrons of molecular oxygen to water with the concomitant oxidation of an electron of L-ascorbate or vitamin C, in the apoplast of plant cells (González-Reyes et al., 1994 ; de Pinto and De Gara, 2004; Pignocchi and Foyer, 2003). Until now, the participation of OA in the growth of bean roots of 4 days of age has been studied, both under conditions stimulating growth with auxin, and under conditions inhibiting growth due to the elicitor OGA10. These results suggest that AO activity may be important for growth (Hernández-Mata and Soriano-Bello, 2003). To continue with the study of the biological function of AO in the development of beans, the specific activity of the enzyme in different parts of the plant was measured during all the phenological stages. Likewise, the dry weight of each organ was determined and the length of the root and stem was measured as growth parameters.

En México, el frijol tiene una gran importancia económica y nutricional, siendo la leguminosa más consumida en el país (SAGARPA), de ahí lo fundamental del estudio de su desarrollo, el cual se divide en cinco etapas fenológicas: germinación, crecimiento vegetativo, floración y llenado de grano. Este desarrollo se ve afectado por los factores ambientales, como, por ejemplo, la falta de agua. En el desarrollo de plantas tales como cebolla, tabaco y chícharo, se ha visto que la enzima Ascorbato Oxidasa (AO) juega un papel importante en la expansión y diferenciación celular, en el control del estado redox del apoplasto e inclusive, en la regulación de la disponibilidad de oxígeno en las células dependiendo de su alta o baja tasa respiratoria. Esto debido a que la AO lleva a cabo la reducción con cuatro electrones del oxígeno molecular a agua con la concomitante oxidación de un electrón del L-ascorbato o vitamina C, en el apoplasto de las células vegetales (González-Reyes et al., 1994; de Pinto y De Gara, 2004; Pignocchi y Foyer, 2003). Hasta ahora se había estudiado la participación de la AO en el crecimiento de las raíces de frijol de 4 días de edad, tanto en condiciones estimulantes del crecimiento con auxina, como en condiciones inhibitorias del crecimiento por efecto del elicitor OGA10. Estos resultados sugieren que la actividad de AO puede ser importante para el crecimiento (Hernández-Mata y Soriano- Bello, 2003). Para continuar con el estudio de la función biológica de AO en el desarrollo del frijol, se midió la actividad específica de la enzima en diferentes partes de la planta durante todas las etapas fenológicas. Así mismo, se determinó el peso seco de cada órgano y se midió la longitud de la raíz y tallo, como parámetros de crecimiento.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2006-0003; Ascorbato oxidasa; Desarrollo; Frijol; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3817